Antibiotic Resistance Pattern and Detection of Some ESBL Genes amongDiarrheagenic E. coli O157:H7. - Faiq, Sivan Tariq; Abdulrahman, Zirak Faqe Ahmed (Sulaimani Journal for Pure and Applied Sciences, 2015)
During the period of 20th of May to1st of November 2013, twenty five isolatesof E. coli O157:H7 were identified among 200 samples taken from children under ten years old suffer from diarrhea (68 males and 132 females) admitted to Rapareen Pediatric hospitals in Erbil City. Isolates were identified from stool sample by using cultural, morphological, biochemical characteristics and serological test. Antibiotic sensitivity testing was done for all isolates by using fourteen antibiotic types The resistance rate of the isolates toward these antibiotics were 100 % for AMP, 96% for MET, 76% for CTX, 72% for TE and KF, 68% for TMP, 56% for FEP, 52% for C and SXT, 48% for CRO, 28% for AK, 20% for CIP, while the lowest percent 16% was for CN, and all isolates were sensitive for IPM. Extended spectrum ß-lactamase (ESBL) production was done for all isolates .Out of 25 E. coli O157:H7isolates, 8(32%) were ESBL producers, while17(68%) were non ESBL producers. The plasmid profile of 25 isolates conducted by using gel electrophoresis, the results revealed different bands with molecular weight ranging between (2kbp- more than 10kbp) in size. The transformation process conducted successfully for (E1 and E15) and the results showed that the resistance genes for ampicillin, Cephalothin, Cefepime, metronidazole and trimethoprimwere located on plasmid DNA for E1 isolate, while for E15 isolate, the ampicillin, Cephalothin, Cefepime, ceftriaxone, Cefotaxime, metronidazole and trimethoprimlocated on plasmid. The results of transformation confirmed by gel electrophoresis, and showed that one plasmids of E1 and two plasmid E15 had been transformed successfully with molecular weight of more than 10 Kbp. All E. coli O157:H7isolates were screened for the presence of ESBL genes including (blaCTX-M - blaSHV-and blaTEM) on plasmid DNA using polymerase chain reaction (PCR) assay. Results showed that all isolates were positive for the existence of ( blaSHV-and blaTEM), while 88% of the isolates contained( blaCTXM) .
Keywords: E coli O157H7 antibiotic resistance plasmid profile transformation ESBLs genes